79=(5x+4)+(8x-3)

Simple and best practice solution for 79=(5x+4)+(8x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 79=(5x+4)+(8x-3) equation:


Simplifying
79 = (5x + 4) + (8x + -3)

Reorder the terms:
79 = (4 + 5x) + (8x + -3)

Remove parenthesis around (4 + 5x)
79 = 4 + 5x + (8x + -3)

Reorder the terms:
79 = 4 + 5x + (-3 + 8x)

Remove parenthesis around (-3 + 8x)
79 = 4 + 5x + -3 + 8x

Reorder the terms:
79 = 4 + -3 + 5x + 8x

Combine like terms: 4 + -3 = 1
79 = 1 + 5x + 8x

Combine like terms: 5x + 8x = 13x
79 = 1 + 13x

Solving
79 = 1 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
79 + -13x = 1 + 13x + -13x

Combine like terms: 13x + -13x = 0
79 + -13x = 1 + 0
79 + -13x = 1

Add '-79' to each side of the equation.
79 + -79 + -13x = 1 + -79

Combine like terms: 79 + -79 = 0
0 + -13x = 1 + -79
-13x = 1 + -79

Combine like terms: 1 + -79 = -78
-13x = -78

Divide each side by '-13'.
x = 6

Simplifying
x = 6

See similar equations:

| 2/12=1/12d | | 2(5m-3)=24 | | -11=-3x | | 5x+c=us | | -10x^2+225x-1025=0 | | 40-6(x-2)=-2 | | 8x+6(-2x+5)=2x-18 | | .66x-1.66=.5x+.83 | | 10x+12-5x+6=-12 | | 4c+23=2+5b | | 4x-15=-95 | | 5n-16-8n=19 | | 26.02*2.006= | | -10x^2+285+650=0 | | 68=2l+(12+2w) | | 3(k+8)+3=2k-7 | | 0.3*0.9= | | 5(x+2)+3=6(3x+9)-2 | | 5Xv-18-4=-36 | | 1/2k-3=-9x-4 | | 4/5=10/3x | | 3/4x-2/3=7/12 | | 3x^2-42x+135=0 | | 4/5=10/3 | | 1-9/5x3 | | -8g+10=-10-12g | | x+-4=-15 | | X=4(1)+8 | | p-25/140=12/42 | | 15/16x=11 | | 4x^2(x^2+6xy-7y^2)=x | | .6(x+8)-.8(5x+2)=10 |

Equations solver categories